Adherence to the dietary approaches to stop hypertension (DASH) and risk of pancreatic steatosis - Danial Fotros; Mohsen Shaygan Tabar; Maedeh Chegini; Mohammad Bahrizadeh; Amir Sadeghi; Amirhassan Rabbani; Zahra Yari; Azita Hekmatdoost (BMC, 2024)
Abstract Background The Dietary Approach to Stop Hypertension (DASH) has shown positive effects on various health factors that may be related to pancreatic steatosis (PS). This study aimed to investigate the association between adherence to the DASH diet and the risk of developing PS. Methods This case-control study was conducted on 278 patients diagnosed with gallstone disease and referred to Taleghani Hospital (Tehran, Iran). Among the participants, 89 were diagnosed with PS based on an endoscopic ultrasound (EUS) examination, while 189 patients did not exhibit this condition. The dietary intake of patients was assessed using a validated food frequency questionnaire (FFQ). Participants were classified based on the DASH diet score. Multiple logistic regression models estimated crude and multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs). Results The mean ± SD of DASH score in PS patients and controls was 23.68 ± 4.38 and 25.27 ± 4.2, respectively (P = 0.006). The risk of PS in the highest tertile of DASH score was 64% lower than the lowest tertile (OR = 0.36, 95%CI: 0.17-0.75, P = 0.005) after full adjustment for confounders. Also, more intake of vegetables and whole grains and less intake of sodium, red and processed meat were each significantly associated with reduced risk of PS. Conclusions Our data prove that adherence to the DASH diet was associated with a lower risk of PS. Further prospective studies are warranted to confirm these associations and explore the underlying mechanisms.